2013
DOI: 10.1108/ijpcc-07-2013-0017
|View full text |Cite
|
Sign up to set email alerts
|

Mobile‐based interpreter of arterial blood gases using knowledge‐based expert system

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…With regard to the advances in the use of oxygen measurement devices or pulse-oximeters, several studies and approaches [ 12 , 40 , 41 , 42 , 43 , 44 ] highlight the different criteria for their placement and the interpretation of the results obtained. As for the second research line mentioned, all the reviewed works [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ] have been already described in Section 1.4.2 . Generally, all of them propose systems that, starting with the pulse-oximeter readings, implement predictive solutions based on different technical approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the advances in the use of oxygen measurement devices or pulse-oximeters, several studies and approaches [ 12 , 40 , 41 , 42 , 43 , 44 ] highlight the different criteria for their placement and the interpretation of the results obtained. As for the second research line mentioned, all the reviewed works [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ] have been already described in Section 1.4.2 . Generally, all of them propose systems that, starting with the pulse-oximeter readings, implement predictive solutions based on different technical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Even if at that moment the results were not satisfactory enough, as the accuracy obtained was low, the authors concluded that the bagged complex trees approach used resulted to be the best one. Lastly, it is also of interest to mention the work by Al-Taee et al [ 51 ], in which a tool for mobile devices is proposed that allows to provide help in the making of decisions associated to the interpretation of gasometry results.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos autores de manera previa han optado por la creación de herramientas tecnológicas para facilitar la interpretación de los trastornos en mención con el objetivo de disminuir las repercusiones que pueden traer al paciente, en el año 2013 Taee et al [17] miembros de la escuela de computación y sistema de la información de la Universidad de Kingston ( Reino Unido) conscientes de que los gases son una herramienta indispensable para evaluar y monitorear pacientes críticamente enfermos diseñaron un prototipo para la identificaron del desequilibrio ácido -base y de oxigenación, dicho prototipo fue puesto a prueba a partir de 74 muestras de gases en sangre extraída de la literatura médica y la práctica clínica. Los resultados mostraron que Universidad de Manizales -Facultad de Ciencias de la Salud los trastornos evidenciados por esta aplicación correspondían a los calculados por los pares.…”
Section: Discussionunclassified
“…Such a problem can be minimized or prevented through utilizing computerized medication prescription approaches with a clinical decision support system (CDS) [12][13][14][15] and electronic medical records. These technology-based approaches and many others have been proven to be important in various health care aspects including diagnoses and CDS, 15 remote patient monitoring, 16 as well as improving workflow efficiency. 17 Implementation of a computerized physician order entry (CPOE) system with CDS has been shown to reduce various medication prescription errors, such as dispensing inaccuracies and drug choice errors.…”
Section: Introductionmentioning
confidence: 99%